The Urgency of Improving Public Services in the Digital Era through Electronic-Based Government Systems - Haryono, Andri; Nuryati, Deti (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This research examines the implementation of public policies with the objective of improving public administration services in the digital era. The application of digital technology offers the government the potential to deliver services that are more efficient, accessible, transparent, and participatory. Nevertheless, the implementation of public policies encounters obstacles, including the digital divide, resistance to change, budgetary constraints, and data security concerns. This study examines the factors that facilitate or impede the implementation of policies and formulates strategies and recommendations to optimize public administration services in the digital era. The results demonstrate that the implementation of strategies, including the expansion of human resources, the development of information and communication technology infrastructure, the streamlining of service processes, the formation of collaborative partnerships with stakeholders, and the formulation of responsive and adaptive policies, can facilitate the positive transformation of public administration services in the digital era. This transformation can be evidenced by enhanced efficiency, accessibility, transparency, community participation, and community satisfaction.